Application of Water-Plugging Grouting Material in Water-Rich Fracture Zone of Deep-Buried Tunnel - LI Xiaobing (Renmin Zhujiang)
Considering the water inrush disaster occurred in a deep-buried drill-and-blast tunnel passing through the water-rich fracture zone,this paper analyzes the characteristics of the water inrush disaster and the special requirements for the performance of water-plugging grouting materials.According to the engineering characteristics,grouting materials for water plugging of deep-buried tunnels are prepared,such as ordinary paste,quick-setting paste,and water-plugging slurry mixture.Different performance characteristics of these materials are tested,and the test section is selected for application verification.The results reveal that the water-plugging grouting material developed in this paper has strong impact resistance and water dilution resistance,and the setting time is adjustable and controllable.It can adapt to the water inrush conditions of various flow rates and flows and can effectively block the water inrush point of the deep-buried tunnel in the water-rich fracture zone and clog the water inrush channel.The research results can reduce the risk of water inrush and collapse in a deep-buried tunnel passing through the water-rich fracture zone.